Risk Factors for Asthma in a Helminth Endemic Area in Bahia, Brazil - Luciana S. Cardoso; Daniela M. Costa; Maria Cecília F. Almeida; Robson P. Souza; Edgar M. Carvalho; Maria Ilma Araujo; Ricardo R. Oliveira (Journal of Parasitology Research)
Protective factors associated with atopy or asthma in rural areas include socioeconomic level, overcrowding, and helminth infection. However, little epidemiological information was originated from schistosomiasis areas. This study aimed to investigate factors associated with asthma in a schistosomiasis endemic area. A questionnaire was used to obtain information on demographics, socioeconomic, and environmental features. The ISAAC questionnaire was used to identify individuals with asthma. Parasitological exam was done in all participants and skin prick test to aeroallergens in all asthmatics. Prevalence of Schistosoma mansoni infection was 57.4% and Ascaris lumbricoides, 30.8%. Asthma was found in 13.1% of the population, and 35.1% of them had a positive SPT. Active and passive smoking was positively associated with asthma, whereas A. lumbricoides was negatively associated. In a schistosomiasis hyperendemic region, current infection with A. lumbricoides is protective against asthma. However, we cannot rule out the involvement of S. mansoni infection in this process.